Effect of extrusion cooking on physical and thermal properties of instant flours: a review - Pismag, Remigio Yamid; Rivera, Juan David; Hoyos, José Luis; Bravo, Jesús Eduardo; Roa, Diego Fernando (Frontiers in Sustainable Food Systems, 2024)
The production of instant flour constitutes a fast-expanding sector, and, this is an innovative area, that is being modified adjusting continually its methodologies to enhance production efficiency, optimizing its resources, fostering innovation in its applications, and increasing its economic income. Among the methods widely cited for precooked flours production are spray drying, drum drying, and extrusion cooking, the latter emerging as a high-potential and versatile solution to produce such commodities. In this regard, a comprehensive understanding of the extrusion process, its mechanical principles, and its effects on the physical characteristics of extruded raw materials is necessary. Analyzing process parameters (specifical mechanical energy and mean residence time) is essential to achieve the desired outcomes. Furthermore, it was analyzed the effect of the process modification conditions (temperature, screw speed, and moisture content) on the physical characteristics of the extruded instant flours. This review offers insights into the most reported system parameters as Specifical Mechanical Energy (SME), Pressure, Torque and, physical properties assessed in different instant flour obtained by extrusion such as Water Absorption Index (WAI), Water Solubility Index (WSI), Swelling Power (SP), Rehydration Capacity, Wetting Capacity, Sinking, Dispersibility, Pasting properties, Thermal properties, and Color. The review summarized and discussed the behavior of the hygroscopic properties and the water affinity of different instant flours obtained by extrusion.